2018
DOI: 10.1111/ijlh.12864
|View full text |Cite
|
Sign up to set email alerts
|

Use of D‐dimer in oral anticoagulation therapy

Abstract: Individualized anticoagulation management and improvement of the safety and effectiveness of oral anticoagulant have always been the focus of clinicians' attention. D‐dimer, a sensitive marker of thrombosis and coagulation activation, is not only traditionally used in the diagnosis of venous thromboembolism, acute aortic dissection, and disseminated intravascular coagulation but can also be used as a helpful marker in the management of oral anticoagulant, including evaluating the anticoagulation quality, predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 61 publications
0
37
1
1
Order By: Relevance
“…Elevated D‐dimer was always associated with unfavorable events 20,21 . Previously, the lack of specificity has been regarded as a disadvantage of D‐dimer 7 . However, low specificity has been transformed into one of its advantages in the evaluation of prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated D‐dimer was always associated with unfavorable events 20,21 . Previously, the lack of specificity has been regarded as a disadvantage of D‐dimer 7 . However, low specificity has been transformed into one of its advantages in the evaluation of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early and effective predictors of clinical outcomes are urgent needed for risk stratification of Covid‐19 patients. D‐dimer originates from the formation and lysis of cross‐linked fibrin and reflects activation of coagulation and fibrinolysis 7 . It has been reported that Covid‐19 was associated with hemostatic abnormalities, and markedly elevated D‐dimer levels were observed in those nonsurvivors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer levels as marker of hypercoagulable state and intravascular thrombosis are frequently increased in clinical settings including severe infections, sepsis, deep vein thrombosis, and pulmonary embolism [ 38 , 39 ]. Elevated levels of D-dimer and its association with poor clinical outcomes were reported in patients with COVID-19 in a recent study and a D-dimer level of >2.0 µg/mL on admission (fourfold increase) effectively predicted inhospital mortality in patients with COVID-19 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The challenge was to find effective predictors of COVID-19 critical disease and death in order to identify critical patients early. Elevation of D-dimer indicated an hypercoagulable state in patient with Covid-19 and reflects activation of coagulation and fibrinolysis [ 3 ]. Recent literature data show that D-dimer values are frequently enhanced in non-survivor patients with COVID-19 [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%